CAPITAL STRUCTURE AND THE PERFORMANCE OF DEVELOPMENT FINANCE INSTITUTIONS IN NIGERIA - Ngutor, Anyam; Nguwasen, Kwahar; Teryima, Sev Joseph; Terungwa, Jato Paul; Sylvia, Sev (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
The study investigated the effect of capital structure on the performance of selected Development Finance Institutions (DFIs) in Nigeria. The study specifically examined the effect of Total Debt to Total Assets (TDTA) on performance of selected of development finance institutions in Nigeria; and ascertained the effect of Total Debt to Total Equity (TDTE) on performance of selected development finance institutions in Nigeria. The study adopted an ex-post facto research design and data were collected from published annual financial records of the selected DFIs on both TDTA and TDTE, the independent variables and Return on Assets (ROA), the dependent variable, for a period of ten (10) years (2013-2022). The population of the study composed of seven (7) national DFIs namely: Central Bank of Nigeria (CBN), Bank of Agriculture (BOA), Bank of Industry (BOI), Development Bank of Nigeria (DBN), Federal Mortgage Bank of Nigeria (FMBN), Nigeria-Export-Import Bank (NEXIM) and the Infrastructure Bank Plc (IBN). The study sampled four (4) national DFIs using a purposive sampling technique, including CBN, BOI, FMBN and NEXIM. Computation of the relevant ratios were done for the independent variables (TDTA and TDTE); and the dependent variable (ROA). Data analysis was done using multiple regression and the econometric technique of Dynamic Ordinary Least Squares (DOLS) with the aid of E-Views Version 13. The study found that TDTA has a negative but significant effect on ROA, indicating that a percentage change in TDTA leads to lower ROA by 0.071551 and TDTE has a positive effect of TDTE on ROA, showing that a percentage change in TDTE will significantly increase ROA by 0.001696. The study concluded that the investigated DFIs have low equity capital which seems to hinder their ability to attract large loans for operations. The study recommended amongst others that DFIs should maintain a balanced total debt to total assets (TDTA) and ensure the regular monitoring of the debt-to-asset ratio to ensure it remains within a healthy range which will help maintain a balance between leveraging and risk.